Development of upright, multimodal, respiratory MRI - Harkin, James (2020)
Respiratory diseases can have a severe impact on people's quality of life and life expectancy. To investigate these diseases, CT and spirometry are the current "gold standards" used by clinicians. In tandem, CT and spirometry, offer high resolution images and lung function information. However, CT exposes the patient to ionising radiation, making multiple investigations undesirable. The results of pulmonary function tests, such as spirometry, are also variable and depend on the effort levels of the patient. In addition, the information provided from most pulmonary function tests is a global measure; abnormal values may only occur when a large region of the lung is affected. These issues mean that, using current measures, it can be difficult to diagnose respiratory diseases and track their progression to see if a particular treatment is being effective.